POLY(ETHYLENE) OXIDE SYNTHETIC POLYMER HYDROGELS FOR MEDICAL APPLICATIONS - Haryanto, Haryanto (PROSIDING SENATEK FAKULTAS TEKNIK UMP, 2015)
Recently, syntheticpolymer hydrogels have emerged as a promising biomaterial for biomedical applications because of their biocompatibility, water absorption capability, degradability and better mechanical properties than natural polymer hydrogels. Therefore,the current study was undertaken with the main objective of developing modified poly(ethylene oxide) (PEO) hydrogel films with poly(ethylene glycol) diacrylate (PEGDA), poly(ethylene glycol) dicarboxcylate (PEGDC), poly(ethylene glycol) dimethacrylate (PEGDMA) and hyperbranchpolyglycidol (HPG) with enhancedproperties using electron beam (E-Beam) for three major applications namely wound dressing, anti-adhesion barrier and tissue engineering scaffold. Cross-linked PEGDA/PEO hydrogel was developed for wound dressing application. Thecross-linked PEGDC/PEO and PEGDMA/PEO hydrogels were developed for an anti-adhesion barrier application.And a microporous hydrogel scaffold was developed from HPGand PEO using e-beam induced cross-linking for tissue engineering applications.This study shows the potential ofmodified PEO hydrogel films in biomedical applications especially as wound dressing, anti-adhesion barrier and tissue engineering scaffold. Keywords: crosslinkedhydrogel,e-beam, poly(ethylene) oxide, electron beam,biomedical applications.